ANALISIS PENGELOLAAN ALOKASI DANA DESA DI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Sholihat, Walmi; Sari, Ria Nelly; Ratnawati, Vince (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2017)
This research focuses on the application of the management of the Village Fund Allocation for the purpose of describing do management of Village Fund Allocation has been running according to the rules and regulations. This research was conducted because management of the Village Fund Allocation not in accordance with applicable regulations.This research is expected to be beneficial to the Indragiri Hulu district government, especially subdistrick Seberida in an effort to realize good governance the management of Village Fund Allocation. This research was conducted in villages in the subdistrict Seberida, as one implementaion location management of the Village Fund Allocation. The research is done by interviews deeply to village officials competent then by means of data collection of Bapemas- Pemdes Indragiri Hulu district.The results of this study indicate that for the planning, implementation and responsibility management of the Village Fund Allocation, has revealed the existence of participation, transparency, and accountability although there were a number of problems was still going on in the management of Village Fund Allocation. The main constraint is the lack of socialization from the district government related the management of Village Fund Allocation then still found human resources remain low that requires assistance from a team to control the subdistrict or district control team sustainably.